2015
DOI: 10.1179/1362171814y.0000000271
|View full text |Cite
|
Sign up to set email alerts
|

Control of mass and heat transfer for steel/aluminium joining using Cold Metal Transfer process

Abstract: The Cold Metal Transfer process is investigated to join zinc coated steel with aluminium alloy by braze-welding. A 4043 filler metal is deposited on the surface of the coated steel, and the effect of the current waveform on the metal transfer and the heat transferred to the base metal is investigated. The reduction in the 'boost phase' duration of the current waveform decreases the volume of liquid drops at the wire tip and allows to increase the short-circuit frequency, inducing a similar or higher deposit ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…[69] This was also observed in recent CMT welding of aluminum alloy A 6061 T6 with galvanized steel DP 800 using the filler alloy Al-3Si-Mn [70] and in CMT weld deposition of filler alloy A 4043 (Al-5Si) onto galvanized steel S235. [71] The results of the current study confirm this trend: the mean thickness of the IM layer, x, tends to increase with heat input, E, as illustrated by the ascending trend line in Figure 6. It must be pointed out that this line visualizes the general trend taking into account x from all experiments conducted.…”
Section: B Influence Parameters On the Layer Thicknesssupporting
confidence: 71%
See 1 more Smart Citation
“…[69] This was also observed in recent CMT welding of aluminum alloy A 6061 T6 with galvanized steel DP 800 using the filler alloy Al-3Si-Mn [70] and in CMT weld deposition of filler alloy A 4043 (Al-5Si) onto galvanized steel S235. [71] The results of the current study confirm this trend: the mean thickness of the IM layer, x, tends to increase with heat input, E, as illustrated by the ascending trend line in Figure 6. It must be pointed out that this line visualizes the general trend taking into account x from all experiments conducted.…”
Section: B Influence Parameters On the Layer Thicknesssupporting
confidence: 71%
“…This corresponds to fundamental diffusion kinetics [69] and to previous CMT experiments considering different heat inputs. [70,71] Fig. 9-Merged optical micrograph of the joint cross section of sample 08 (a).…”
Section: Influences Of the Torch Type And The Torch-workpiece Distmentioning
confidence: 99%
“…From the results in Figs. 4 and 8, it was indicated that the smooth surface in zone A was NiAl, and the ridge-like zone mainly consisted of NiAl 3 . Under the action of shear force, a crack formed in the IMC layer.…”
Section: Fracture Morphologymentioning
confidence: 98%
“…At the same time, the return signal is provided to the wire feeder which gives the wire a back-drawing force. This phase assists in the liquid fracture and transfer of material into the welding pool [39]. The complex waveform of the welding current in the CMT process and the 'back feeding' of the filler wire that mechanically forces the metal transfer make it difficult to understand the relation between welding parameters, metal transfer and heat transfer as shown in Fig.1.…”
Section: Cladding Processmentioning
confidence: 99%